Anut Grubyug : Takluknya Petani Pada Mobilisasi Pembangunan (studi Lasus Pada Proyek Pengembangan Jarak Pagar Sebagai Sumber Energi Alternatif Di Kecamatan Tepus, Gunungkidul, di Yogyakarta) (Faculty of Social Science, Universitas Negeri Semarang, 2016)
Villagers especially those living in areas where ecological conditions were dry and barren often the people who have to live in poverty. These conditions encourage the emergence of the will of the state to improve and regulate its citizens through development projects. The name of development, the hands move countries regulate its citizens with a noble purpose, namely improving the standard of living and improve people's lives better than ever. Through the study of the development project Jatropha as an alternative energy source, then this paper tries to parse the ongoing development of the Jatropha project which is run by mobilizing farmers have failed to improve people's lives. The results showed that the mobilization has resulted in an increasingly helpless citizens due to being embraced grubyuk, just went along with the others. The existence of the project to overcome the energy crisis has made farmers fall into another crisis dimension the crisis of self-reliance so that farmers are always looking forward to the next projects. They surrendered totally subservient to the power structure that governs them.